Potential of local material SiO2 water Hyacinth for semiconductor materials - Hidayat, Sony; Ahmad Ziyan Nafis; Muhammad Noorman Perdana; Upik Nurbaiti (Journal of Natural Sciences and Mathematics Research, 2025)
This study aims to examine the potential of local SiO₂ material synthesized from water hyacinth biomass waste as a candidate for semiconductor materials. Synthesis was carried out through a calcination process at temperatures above 600 °C to remove cellulose, lignin, and other impurities. Material characterization was carried out using UV-Vis spectroscopy, X-ray Diffraction (XRD), and Raman Spectroscopy. The results of UV-Vis spectroscopy showed that the water hyacinth derived SiO₂ exhibited an unusually reduced optical band gap of approximately 2.3 eV, likely influenced by impurity phases.. XRD tests indicated the presence of two crystal phases, namely the trigonal structure of SiO₂ and the monoclinic structure of the CaH₁₂O₁₇Si₂U₂ compound. Raman analysis confirmed the presence of functional groups such as Si, amorphous SiO2, CH₂/CH₃ and vibration signals from irregular sp² carbon. This combination of structures is thought to cause a lower band gap value compared to pure SiO₂. This finding indicates that SiO₂ from water hyacinth has potential as an intermediate semiconductor material, although further purification is still needed to increase the purity of the SiO₂ phase.